69.7k views
5 votes
3x + 5y = -27
|-7x - 5y = 3

User Ptr
by
5.2k points

1 Answer

2 votes

Answer:

(x, y) = (6, -9)

Explanation:

Add the two equations to eliminate the y-variable:

(3x +5y) +(-7x -5y) = (-27) +(3)

-4x = -24 . . . simplify

x = 6 . . . . . . divide by -4

Substitute this value of x into the first equation and solve for y:

3(6) +5y = -27

5y = -45 . . . . . . . subtract 18

y = -9 . . . . . . . . . divide by 5

The solution to this system of equations is (x, y) = (6, -9).

User Green Fire
by
6.7k points